STRONG II trial: stereotactic body radiation therapy following chemotherapy for unresectable perihilar cholangiocarcinoma – a single-arm multicentre phase II study - Derk Jan de Groot; Luisa Vonghia; Bas Groot Koerkamp; Lydi M J W van Driel; Alejandra Méndez Romero; Anne Demols; Erik van Werkhoven; Dirk De Ruysscher; Christelle Bouchart; Marjolein Y V Homs; Joris I Erdmann; Martijn Intven; et al. (BMJ Open)
Introduction For patients with perihilar cholangiocarcinoma (pCCA), surgical resection remains the sole treatment modality that can potentially result in cure. Unfortunately, the majority of patients present with unresectable tumours or are excluded from surgical treatment due to complications like cholangitis affecting their performance status. In the Netherlands, recommended first-line treatment for patients with unresectable pCCA is palliative chemotherapy with gemcitabine and cisplatin. This regimen yields an estimated median overall survival (OS) of 11.7–15.2 months, highlighting the urgent need for novel treatment options. The STRONG I trial, a phase I study in patients with unresectable pCCA, was completed in 2020. Its aim was to assess the feasibility and toxicity profile of adding stereotactic body radiation therapy (SBRT) to chemotherapy. SBRT, delivered in 15 fractions of 4.0 Gray (Gy), was considered to be feasible and safe, with no dose-limiting toxicity being observed. The 1-year local tumour control rate was 80% and the 1-year OS rate 100%, with maintenance of quality of life (QoL). These results encouraged us to initiate the STRONG II trial, aiming to investigate the efficacy of adding SBRT to chemotherapy in a larger patient cohort.Methods and analysis STRONG II is a single-arm, multicentre phase II study. Patients with non-metastatic unresectable pCCA (T1-4, N0-2) are eligible. A total of 30 patients will be enrolled in six academic centres in the Netherlands and two in Belgium. SBRT will be delivered in 15 fractions of 4.0–4.5 Gy. The primary endpoint is local tumour control, defined by Response Evaluation Criteria in Solid Tumours (RECIST) V.1.1. Secondary endpoints include toxicity, biliary stent-related events, progression-free survival, OS and QoL using the EuroQoL five-dimensional, five-level (EQ-5D-5L) questionnaire, European Organisation for Research and Treatment of Cancer (EORTC) Quality of Life Questionnaire - Core 30 (QLQ-C30) and the EORTC Biliary Module (QLQ-BIL21). In addition, we will explore the predictive value of the peripheral immunological status (immune-related proteins and serum functional immunological status assay) and its dynamics in determining survival outcomes. For this explorative translational study, two blood samples will be collected, one before the start of chemotherapy and another after completing chemotherapy.Ethics and dissemination Approval of the study was obtained on 5 June 2024 by the Medical Ethics Review Committee of Erasmus Medical Center Rotterdam, the Netherlands (ID: NL86210.078.24). The anticipated time frame for patient enrolment is July 2024 to December 2027. The main study findings will be published in peer-reviewed medical journals, and presented at national and international conferences.Trial registration number NCT06493734 (ClinicalTrials.gov).